Ready-To-Eat Rice in Retort Pouch Packaging as an Alternative Emergency Food Product - Sri Rahayu; Tjahja Muhandri; Dase Hunaefi; Philipp Fuhrmann; Iryna Smetanska (Jurnal Teknologi dan Industri Pangan, 2022)
Recently, the rising incidence of natural catastrophe has increased the disaster preparedness, aiming to mitigate its devastating effect. Developing an emergency food is one of meaningful attempts to rise the preparedness. This research aimed to determine the best formula of ready-to-eat rice in retort pouch packaging accepted by consumers, and to determine the operating time to reach a lethality value (F0) to meet the commercial shelf-stable food requirements as an emergency food. The thermal process adequacy (F0) was used to determine the commercial shelf-stable products according to Indonesian regulation. The results showed that the determination of ready-to-eat rice was dependent on the ratio of rice and water. The most accepted product was determined according to quality attributes and organoleptic tests applied to meet the criteria for emergency food, namely color, flavor, and texture and best perceived by consumers. A formula with 140 g of half-cooked rice and 60 g of water was attributed to the best sample, having hardness of 7305.45 gf, elasticity of 36.40%, gumminess of 2185.720 gf, and adhesiveness of -167.975 g.s. In terms of microbiological quality, the TPC for the half-cooked rice sample reached 7.2×107 CFU/mL, while cooked rice in retort pouch packaging was <25 CFU/mL. Using heat distribution curve, heating at 110°C produced a come up time (CUT) after 40 min. Furthermore, the F0 value was 4.12 which was in accordance with the Indonesian regulation.